STUDYING THE EFFECT OF THE PRELOAD INDUCED BY SCREW TIGHTENING ON STRESS DISTRIBUTION OF A DENTAL IMPLANT - Belagh, Alireza Bidar Farrokh; Kashani, Hamed Moayeri (MATTER: International Journal of Science and Technology, 2017)
The success of implants is largely dependent on initial stability and long-term osseointegration due to optimal stress distribution around the bone and implant. The purpose of this study is the numerical analysis of stress distribution in jaw bone and implant using finite element analysis considering the static forces caused by screw tightening and masticatory preloads. These forces and design limitations have been applied in accordance with implant science in dentistry to provide a proper stress distribution. First, all the parts were modelled with Solidworks software and then transferred to Abaqus software for analysis and applying the forces. For a better and more exact stress distribution analysis in the bone and implant, this analysis was conducted by two steps, that after determining the properties of each part, boundary conditions, loading and finally meshing the complex using hexahedral meshes and Match mesh technique, the abutment was tightened inside the implant with different tightening torques through six tests to apply preload in first step which this force applying induced stress in jaw and implant. Then, the amount of jaw force was applied to the crown surface. The results showed that the preload is quite effective in bone and implant stress distribution. However, its value only affects the surface stresses of the implant and has little effect on the of jaw bone stress value. This study can be carried on to evaluate the implants life considering Preload.